Applications of green materials for the preparation of eco-friendly bricks and pavers - Vamsi Krishna, B; Rakesh Reddy, E (International Journal of Engineering and Technology, 2018)
The most basic and primary building material for construction of houses is the conventional brick. The rapid growth in today’s construction industry has obliged the civil engineers in searching for more efficient and durable alternatives far beyond the limitations of the conventional brick production [1-2]. A number of studies have been made and serious steps have been taken in manufacturing of bricks  from several waste materials. However, the traditional mean of bricks production which has brought hazardous impacts to the context has not yet been changed or replaced by more efficient and sustainable one [3], [4]. Most of the researches went through enhancing the clay brick quality and properties by mixing the clay with various recycled wastes as foundry sand, granite sawing waste, harbour sediments, perlite, sugarcane, baggase ash, clay waste and fine waste of boron, sewage sludge, waste glass from structural wall and other different wastes. Compile this state of the art work of manufacturing bricks in the past and the current trend in the bricks industry with respect to the raw materials, ways of manufacturing and the out- comings.This project presents an experimental study on the utilization of waste materials which replaces clay with (Plastic covers, Ceramic Powder, Egg Shell Powder, GGBS, Silica Fume, Rice Husk Ash and Lime Powder) and Fine Aggregate with (Recycled glass, Dry Grass, Dead Leaves, Tree barks powder, Sugar cane powder, crumbed rubber) to produce eco-friendly Bricks. This project is an attempt to fill the gap of the past studies and suggest more sustainable and sophisticated methods of brick manufacturing in the future. 40 percent replacement of fine aggregate with crumbled rubber and dry grass in mortar bricks have given encouraging results, also the replacement of cement by egg shell powder at 20% has given a considerable result